Lesson learned: Taiwan touchscreen-maker wintek guessed wrong on where the market was going, lost most of its business with apple and ended up in bankruptcy - Jennings, Ralph (--SIngapore: Forbes Asia, 2015)
Taiwan touchscreen-maker Wintek guessed wrong on where the market was going, lost most of its business with Apple and ended up in bankruptcy.
Keywords: Business failures